Administration of Guidance and Counselling Programme in Nigerian Higher Institutions: Problems and Solutions - Ogunode Niyi Jacob; Akaeze Fidelia Obioma (International Journal on Integrated Education, 2021)
Guidance and Counselling Programme is one of the educational programme that higher institutions are offering in Nigeria. Guidance and Counselling Programme is vital to the development of a stable society. Guidance and Counselling Programme is facing many problems in the Nigerian higher institutions. This paper looks at the administrative problems facing the administration of Guidance and Counselling Programme in the Nigerian higher institutions. The writers, used secondary data to support the various points raised in the paper. The secondary data were sourced from both print and online resources. The paper identified inadequate funding, inadequate lecturers, inadequate infrastructural facilities, inadequate instructional materials, strake action, brain-drain and poor research as the problems facing the administration of guidance and counselling programme in the Nigerian higher institutions. To address, these problems, the following recommended: increasing the funding of Guidance and Counselling Programme, employment of more lecturers in Guidance and Counselling departments, provision of more infrastructural facilities, instructional materials, motivation of Guidance and Counselling Programme lecturers and implementation of agreement with unions groups